Adherence to preventive behaviours and risk of COVID-19 infection: a case-control study - Reza Hosseinabadi; Shoorangiz Biranvand; Khatereh Anbari (Medicinski glasnik, 2022)
Aim: To investigate the relationship between adherence to preventive behaviors and risk of COVID-19 infection. Methods: In this case-control study, 491 participants were selected through convenience sampling. First, the samples of the case group (COVID-19 patients) were selected, and then the control group was matched with the case group based on age, gender, and occupation. The criteria for diagnosing COVID-19 for the case group were self-reported positive PCR test or lung involvement on a chest CT scan. Descriptive statistics were used to summarize the results, and an odds ratio was calculated to quantify the magnitude of the association using a 95% confidence interval (CI) and a p<0.05. Results: The results showed that, compared to those who always wear a mask, the risk of contracting SARS-CoV-2 was 3.153 times higher in those who used no masks (95% CI: 0.953-10.434) and 3.779 times higher in those who used masks occasionally (95% CI:1.929-7.37). The participants who never observed physical distancing and handwashing were 2.25 times more likely to get COVID-19 than those who always observed (95% CI:1.719-4.954; OR=2.258). Conclusion: Participants who fail in following the protective measures, especially wearing a mask regardless of its type, had a higher risk of COVID-19 infection. Therefore, it is recommended to use a mask consistently, especially during the peak of COVID-19 waves.
Keywords: handwashing; masks; personal protective equipment; physical distancing